2022
DOI: 10.1126/sciadv.abk0627
|View full text |Cite
|
Sign up to set email alerts
|

First-passage statistics of colloids on fractals: Theory and experimental realization

Abstract: In nature and technology, particle dynamics frequently occur in complex environments, for example in restricted geometries or crowded media. These dynamics have often been modeled invoking a fractal structure of the medium although the fractal structure was only indirectly inferred through the dynamics. Moreover, systematic studies have not yet been performed. Here, colloidal particles moving in a laser speckle pattern are used as a model system. In this case, the experimental observations can be reliably trac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 78 publications
0
6
0
Order By: Relevance
“…We can refer to the studies in which the scale-free dynamics was shown to yield the power-law type MFPT, in which the recurrent diffusion occurring in an equilibrium system has the MFPT of the form, normalM normalF normalP normalT ( r ) r d normalw , where d w represents the walk dimension related to the mean square displacement as Δ r 2 t β with β = 2/ d w . According to the formulation, the effective dimension, d , evaluated above can be interpreted as the walk dimension d w , thus b = 0.3.…”
Section: Resultsmentioning
confidence: 99%
“…We can refer to the studies in which the scale-free dynamics was shown to yield the power-law type MFPT, in which the recurrent diffusion occurring in an equilibrium system has the MFPT of the form, normalM normalF normalP normalT ( r ) r d normalw , where d w represents the walk dimension related to the mean square displacement as Δ r 2 t β with β = 2/ d w . According to the formulation, the effective dimension, d , evaluated above can be interpreted as the walk dimension d w , thus b = 0.3.…”
Section: Resultsmentioning
confidence: 99%
“…Historically, the atom-cooling community was the first to adopt speckle light fields to trap small particles [38]. The last decade has experienced a revival of the technique to tackle questions in mesoscopic physics, where both static and time-varying speckle optical potentials have been used to study the emergence of anomalous diffusion (from subdiffusion to superdiffusion) in colloidal dispersions [36,[39][40][41][42], to tune effective dispersion forces between small colloidal particles [43], to perform standard microfluidic operations, such as particle guiding and sorting [35], to assemble 2D crystal-like and glassy colloidal materials [44], to control collective behaviour in active matter [45], and to reproduce first-passage statistics [46].…”
Section: Giorgio Volpementioning
confidence: 99%
“…There are nevertheless some cases in which they have been employed to alter the random motion of microscopic particles in interesting ways. For example, the forces produced by random light fields have been employed to alter the diffusion of Brownian particles leading also to superdiffusive behavior in the presence of time-varying patterns. ,, …”
Section: Actuation By Other Properties Of Lightmentioning
confidence: 99%